The effect of consuming chicory juice by breastfeeding mothers on neonatal icterus - Shahla Vaziri Esfarjani; Shadi Zinatian; Mahin Salimi (Wolters Kluwer Medknow Publications, 2022)
Objective: Hyperbilirubinemia has been considered one of the most common clinical conditions in newborn babies. As a traditional medicine, chicory distillate may be beneficial in reducing bilirubin. This randomized, double-blind clinical trial was conducted to determine the effect of chicory extract on hyperbilirubinemia in neonates. Methods: The clinical trial was conducted among 154 participants with hyperbilirubinemia. The study group was selected and randomly divided into the control (n = 77) and intervention (n = 77) groups. In the intervention group, breastfeeding women received a 10% solution of chicory distillate (50 ml every 12 h), whereas, in the control group, the participants received sterile distilled water, 50 ml every 12 h. The infants' bilirubin level was measured before and 24, 48, and 72 h after the intervention. Fisher's exact and Chi-square tests were run to examine qualitative data, while a t-test was applied for independent variables. Findings: There was a significant difference between the intervention and control groups (P < 0.001). Within each group, a significant difference was found in bilirubin levels among different sampling times (P < 0.001). Although the bilirubin levels reduced during the time intervals in both groups, the reduction rate was significantly higher in the intervention group (P < 0.001). Based on the results, breastfeeding mothers should be aware of including chicory extract in their nutritional programs. Conclusion: Chicory extract consumption in breastfeeding mothers can reduce bilirubin in their neonate